Exploring Baba and Nyonya culture via multiple image lenses : food travellers' perspective / Jason M. S. Lam...[et al.] - M. S. Lam, Jason; Lee, Sean; Ling, Goh Mei; Melatu Samsi, Siti Zakiah (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA, Puncak Alam Campus, 2017)
This study applies a multidimensional approach in the context of Baba and Nyonya cuisine. A total of 209 international food tourists were surveyed in Malacca, Malaysia. The results derived from structural equation modelling empirically confirmed that the cognitive image dimensions of safety, uniqueness and family-oriented significantly and positively influenced both affective and conative images. However, the cognitive image dimension of variety only partially influenced affective image, but not a conative image, while the cognitive image of cooking methods did not show any significant effects on the affective nor conative image. Finally, affective image dimensions significantly and positively influenced the conative image. Relevant implications, limitations, and suggestions for future studies for Baba and Nyonya cuisine also discussed.